PEMANFAATAN MUSEUM DEMAK BAGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR - Musawamah, Mualamatul; Arsanti, Meilan (Jurnal Ilmiah KONTEKSTUAL, 2025)
The aims of this study were (1) to identify the collection of objects in the Demak Museum, (2) to find out the strategy of PAI teachers in utilizing the Demak Museum for class IV SD BUQ Betengan Demak. This study used a type of field research with a descriptive qualitative approach with Islamic education teachers as subjects and fourth grade students. Data collection techniques with interviews, observation, and documentation. Data analysis by collecting, reducing, displaying, and verifying or drawing conclusions. The results showed that the objects in the Demak Museum that can be used as PAI learning for grade IV through KD 3.21, namely soko tatal, wood chips, mushaf and interpretation of the Koran, drum and kentongan have cultural values. Character education includes religious values, mutual cooperation, historical values, creativity, environmental care, hard work, and discipline. The learning strategy is carried out with the stages of preparation and implementation through the strategy of inviting resource persons. At the end of the lesson the PAI teacher gives advice and moral messages regarding the importance of these positive values so that every student has them and is always being improved.